Guyana Gold: A Unique Resource Curse?. Issue 2 (1st February 2017) - Hilson, Gavin; Laing, Tim
Abstract: This article offers explanations for the underwhelming economic performance of Guyana, a country heavily dependent on the revenue generated from gold mining. Here, government intervention has spawned a gold mining sector which today is comprised exclusively of local small and medium-scale operators. But whilst this rather unique model appears to be the ideal blueprint for facilitating local development, the country seems to be experiencing many of the same setbacks that have beset scores of other resource-rich developing world economies. Unless these problems are anticipated, properly diagnosed and appropriately tackled, a resource curse-type outcome is inevitable, irrespective of the context.